Ending famine in India: a transnational history of food aid and development, c. 1890-1950 - Simonow, Joanna (Global Connections: Routes and Roots, 2023)
The task of ending famine in India was taken up by many at the beginning of the twentieth century. Only decades earlier, famine in India had been believed to be a necessary evil. Now it was the reason for the increasing activities of doctors, nutritionists, social reformers, agricultural experts, missionaries, anti-colonial activists and colonial administrators, all involved in temporary relief and finding permanent solutions to famine